Major Complications in FESS: Tips from Expert Surgeons. (2nd September 2014) - Tewfik, Marc A.; Wormald, Peter J.; Hwang, Peter H.; Carrau, Ricardo L.; Douglas, Richard; Valentine, Rowan
Abstract : Program Description: The risk of serious complications during endoscopic sinus surgery (ESS) is ever present. It is the responsibility of the operating surgeon to minimize the risks through meticulous preoperative preparation, careful operative technique, and diligent postoperative care. This miniseminar brings together some of the top sinus surgeons from around the world to share some of their technical pearls and experience regarding the treatment and avoidance of complications in ESS, as well as the latest research in the field. Through the use of clinical case‐based vignettes, topics that will be covered include CSF leak, orbital injury, and catastrophic hemorrhage. Educational Objectives: (1) Identify high‐risk situations preoperatively in patients undergoing functional ESS (FESS). (2) Apply intraoperative measures and technical pearls to avoid serious complications during FESS. (3) Elaborate a clear plan for the management of intraoperative emergencies, including orbital hematoma and internal carotid artery injury.